A Novel Selective "Turn‐On" Fluorescent Chemosensor Based on Thiophene Appended Cyclotriphosphazene Schiff Base for Detection of Ag+ Ions. Issue 39 (15th October 2021) - Tümay, Süreyya Oğuz
Abstract: The salicylaldehyde‐functionalized cyclotriphosphazene (1 ) and thiophene appended cyclotriphosphazene based Schiff base (2 ) were designed and synthesized. The characterizations were carried out via MALDI‐TOF, FTIR, 13 C, 31 P and 1 H NMR. The photophysical behavior of compound 2 was evaluated by UV‐Vis absorption, time‐resolved fluorescence, excitation‐emission matrix (EEM) analysis, steady‐state fluorescence, and 3D‐fluorescence spectroscopies. Compound 2 demonstrated selective fluorescence "turn‐on" response at 427 nm towards to Ag + ion when the tested competitive species did not affect fluorescence signal. The binding and sensing mechanisms were evaluated by DFT calculations which approved that the PET process between C=N and fluorophore groups was inhibited, and the fluorescence "turn‐on" response was obtained with the contribution of CHEF after 1 : 1 coordination of compound 2 with Ag + ion. The LOD and LOQ were calculated as 3.15 and 9.45 μmol L −1, respectively in the linear range of 9.35–210.00 μmol L −1 Ag + ions. The practical application of compound 2 for Ag + determination was successfully performed in environmental waters after optimization of measurement conditions. The obtained results approved that compound 2 is a selective fluorescent sensor for Ag + ions and it can be used for spectrofluorimetric Ag + determination in real samples. Importantly, according to the literature, this report is the first example of cyclotriphosphazene based fluorescent sensor for Ag + ion. Abstract : A novel thiophene appended cyclotriphosphazene based Schiff base (2 ) was prepared as fluorescent sensor for Ag + ions. The photophysical and fluorescence sensor behaviors were investigated by absorption, time‐resolved fluorescence, excitation‐emission matrix (EEM) analysis, steady‐state fluorescence, and three‐dimensional fluorescence spectroscopies and theoretical calculations. The results approved that 2 can be used for spectrofluorimetric determination of Ag + ions in real samples.